2017
DOI: 10.18203/2394-6040.ijcmph20175328
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity: a rising problem in India

Abstract: Background: Obesity is one of today’s most neglected public health problems. Childhood obesity is one of the most serious public health problems. Obesity causes cluster of non-communicable diseases and creating an enormous socioeconomic and public health burden. Methods: School based cross-sectional study was done in Udaipur city of Rajasthan. Simple random sampling method was used to obtain 1000 study subjects. Questionnaire included their general information, factor contributing to overweight and obesity. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…Similar findings were observed other studies conducted in Udaipur city and Nagpur. 12,26 The present study shows that body fat% is higher in girls as compared to boys. Similar findings are also reported by other studies.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…Similar findings were observed other studies conducted in Udaipur city and Nagpur. 12,26 The present study shows that body fat% is higher in girls as compared to boys. Similar findings are also reported by other studies.…”
Section: Discussionsupporting
confidence: 45%
“…Different school-based data on overweight and obesity in India shows a prevalence of 1.6-27.7% and 1.2-12.4% respectively among adolescents. [6][7][8][9][10][11][12][13][14][15] In Northeastern India, the prevalence of overweight and obesity are 1.9-6.1% and 0.4-0.8% respectively. In the present study, the prevalence of overweight and obesity was found to be 6.4% and 1.2% respectively in Manipur.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations